Seasonal changes in burrow geometry of the common mole rat (Rodentia: Bathyergidae) - Thomas, H.; Scantlebury, M.; Swanepoel, D.; Bateman, Philip; Bennett, N. (Springer Berlin Heidelberg, 2013)
Sociality in mole rats has been suggested to have evolved as a response to the widely dispersed food resources and the limited burrowing opportunities that result from sporadic rainfall events. In the most arid regions, individual foraging efficiency is reduced and energetic constraints increase. In this study, we investigate seasonal differences in burrow architecture of the social Cryptomys hottentotus hottentotus in a mesic region. We describe burrow geometry in response to seasonal weather conditions for two seasons (wet and dry). Interactions occurred between seasons and colony size for the size of the burrow systems, but not the shape of the burrow systems. The fractal dimension values of the burrow systems did not differ between seasons. Thus, the burrow complexity was dependent upon the number of mole rats present in the social group.